Anti-Respiratory Syncytial Virus Mechanism of Houttuynia cordata Thunb Exploration based on Network Pharmacology - Du, Haitao; Ding, Jie; Wang, Ping; Zhang, Guisheng; Wang, Dandan; Ma, Qingyun; Li, Na; Sun, Tiefeng (Combinatorial Chemistry & High Throughput Screening, 2021)
Background and Objective: Respiratory Syncytial Virus (RSV) is the leading cause of infant lower respiratory tract infections with no mature vaccines and medicines available. Pneumonia caused by RSV kills many infants every year. There are unique advantages of Traditional Chinese Medicine (TCM) to fight against the virus. Houttuynia cordata Thunb is a commonly used antivirus medicine in TCM, but its mechanism has not been investigated. The current study explores the anti-RSV mechanism of H. cordata Thunb by means of network pharmacology and bioinformatics. Methods: The candidate compounds of H. cordata Thunb and the potential targets were obtained from the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP), PubMed, CNKI, PubChem Database, and Swiss Target Prediction database. Then the potential targets and pathways of H. cordata Thunb against RSV were screened by GeneCards, GenCLiP 3, and NCBI Database. We developed a Protein-Protein Interactions (PPI) Network and Compound-Target-Pathway Network through the Cytoscape software. Furthermore, core targets were preliminary verified by Gene Expression Omnibus (GEO) database by bioinformatics methods. At last, the first six pathways were screened out to draw a map of the main target signal pathways. Results: A total of 12 potentially active compounds and 47 potential interaction targets were screened. PPI Network and data from GEO showed that IL-6, STAT3, TNF, AKT1, PTGS2, SRC, and MAPK3 may play a core role in the antivirus process. KEGG enrichment pathway analysis predicted that H. cordata Thunb exerted its anti-RSV effect by regulating TNF, Rap1, HIF-1, PI3KAkt, MAPK, and VEGF signaling pathways. Conclusion: This study preliminarily predicted the main active compounds, targets and related pathways of H. cordata Thunb in the treatment of RSV-induced diseases, which laid a good foundation for further revealing its mechanism.
Keywords: bioinformatics